The estimate of convergence rate in the min-schema of multivariate random variables - Arvydas Jokimaitis (Lietuvos Matematikos Rinkinys)
In this paper the nonuniform estimate of the convergence rate for the distribution of the minima of multivariate random variable is obtained.